A Longitudinal Model of Continued IS Use: An Integrative View of Four Mechanisms Underlying Postadoption Phenomena - Kim, Sung S.; Malhotra, Naresh K. (Management Science, 2005)
Although initial use is an important indicator of information system (IS) success, it does not necessarily lead to the desired managerial outcome unless the use continues. However, compared with the great amount of work done on IS adoption, little systematic effort has gone into providing insight into continued IS use over time. The objective of this study is to develop a longitudinal model of how users’ evaluations and behavior evolve as they gain experience with the information technology application. The proposed model is a unified framework that sheds light on four different mechanisms underlying postadoption phenomena: (1) the processes suggested by the technology acceptance model; (2) sequential updating mechanisms; (3) feedback mechanisms; and (4) repeated behavioral patterns. The proposed model was empirically tested in the context of Web-based IS use in a nonexperimental setting. Our findings suggest that, as hypothesized, each of the four theoretical viewpoints is essential for a deeper understanding of continued IS use. We discuss important findings that emerged from this longitudinal study and suggest directions for additional research.